BAGI HASIL DAN BANK SYARI’AH (Solusi terhadap Bunga Bank) - Rudy Haryanto Rudy Haryanto (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2010)
Abstract: To save money in terms of investation is one of bank’s functions. Interest and production sharing are kinds of investation in banking system. Interest is a marketable entry in conventional banking, however production sharing is known in syari’ah banking system. Some people argue that interest cannot be seperated from the banking activity, in fact Islam recommends the followers to avoid it; hence it could be substituted with term of production sharing. It matches the priciple of musyarakah and mudharabah as being taught by Rasûlullâh SAW. Bank interest is considered ribâ (excessive interest) and it is forbidden in Islam. Moreover, production sharing is more useful and beneficial for people. Unfortunately, the value of production sharing (syarî’ah banking product) is lower than the value of banking interest (conventional banking product) due to the fact that the ralationship established by syari’ah banking and its customer is based on the principle of gotong royong (mutual coorporation) and production sharing partnership. Key Words: ribâ, musyarakah, mudharabah, dan bagi-hasil